Isolation and Phylogenetic Identification of Copper-Resistant Bacteria with Hydrocarbon Degrading Ability - Lee, Yan Long (2017)
Two bacteria isolates (4M5 and A4) with hydrocarbon-degrading properties was subjected to copper (Cu) toxicity test at 2.0 mg/L, which is 10x higher than the permissive leve for Cu in industrial effluents according to Malaysian Environmental Quality Regulations. Observation showed that isolate 4M5 was able to survive Cu at tested concentration (p<0.05) whereas A4 failed to survive (p<0.05). Identification test through Gram staining showed isolate 4M5 was Gram-negative, rod-shaped bacterium, whereas isolate A4 was Gram positive, rod-shaped bacterium. DNA of both bacteria isolates was extracted successfully and amplification of 16s rDNA region of the DNA using Polymerase Chain Reaction (PCR) yilded a band size of 800 bp. Result of the PCR product sequencing and BLAST analysis was used to construct a phylogenetic tree successfully, in which isolate 4M5 was identified as Pseudomonas aeruginosa, wheras isolate A4 was found to be Bacillus subtilis. Bacterial Adhesion Towards Hydrocarbon (BATH) Assay using isolate 4M5 showed negative result on production of biosurfactant (p>0.05) when exposed to Cu at 2.0 mg/L. Study on the biodegradation of crude oil co-contaminated by 2.0 mg/L of Cu showed increase in growth of isolate 4M5 by 10-fold (p<0.05) and 67% reduction of crude oil, indicating isolate P.aeruginosa 4M5 was able to biodegrade crude oil even in the presence of Cu at environmentally high level. This suggest the potential use of P. aeruginosa 4M5 in bioremediation strategy to clean up crude oil waste found in mixed industrial effluent.